Engineering a multivalent antibody nanoparticle to overcome SARS-CoV-2 Omicron immune evasion - Sun, Hui; Jiang, Yanan; Lan, Miaolin; Zhou, Ming; Yi, Gangshun; Shen, Juan; Deng, Tingting; Liu, Liqin; Huang, Yang; Li, Yu; Su, Jinfu; Lin, Yanling; et al. (PLOS Pathogens, 2025)
Author summary As SARS-CoV-2 evolves, new variants evade immunity, reducing the efficacy of previously potent antibodies like 1C4. We identified key mutations in the viral spike protein responsible for its loss of neutralization and developed a nanoparticle-based strategy to restore its activity. By enhancing antibody potency through multivalent binding, our approach effectively neutralizes resistant variants and improves protection in animal models. This strategy offers a promising solution to counteract viral immune escape and extend the durability of antibody therapeutics, addressing the challenge of keeping pace with rapidly mutating viruses.